Utilization of the Zoom Application in Improving Arabic Speaking Skills (Mahārah Kālam) during the Covid-19 Pandemic/ Pemanfaatan Aplikasi Zoom dalam Meningkatkan Mahārah Kālam pada Masa Pandemi Covid 19 - Ngindana Zulfa (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2021)
The COVID-19 outbreak arises problems in learning Arabic. Some instructors feel they spontaneously do not require the language environment (bi'ah lughawiyyah) in the teaching and learning process. This obviously has such a broad impact on the four language skills and one of the biggest challenges for them is that they could not teach Arabic speaking skills communicatively. This study aims to offer a considerable insight about the use of Zoom Cloud Meetings in improving Arabic speaking skills (mahārah kālam) during the pandemic. The study used qualitative descriptive methods and the data were collected through interviews and documentation. The data were analyzed using the theory of Miles and Huberman. Based on the review of results of interviews and documentation, Zoom Cloud Meeting is an effective way to improve students’ speech as it provides complete features so that communication between lecturers and students using Arabic can be established properly. To improve these skills, storytelling (taqdimul qisshah) and conversation (muhadatsah) are practiced. As a learning medium, Zoom certainly has advantages and disadvantages. The benefits of this media include having complete features, good access, large, flexible, and high capacity and supporting the teaching and learning process. While the drawbacks of using zoom application are the extra financial burden for internet quota, media restrictions, and having a strong internet connection. Abstrak Kehadiran virus Covid-19 memunculkan permasalahan dalam pembelajaran bahasa Arab. Beberapa pendidik merasa kehilangan bi’ah lughowiyyah pada proses belajar mengajar. Hal ini mengakibatkan empat keterampilan bahasa, khususnya keterampilan berbicara tidak dapat terealisaikan dengan maksimal. Artikel ini bertujuan untuk memberikan wawasan kepada pendidik tentang pemanfaatan Zoom Cloud Meeting dalam meningkatkan mahārah kālam pada masa pandemi. Pada penelitian ini penulis menggunakan metode kualitatif deskriptif, dengan metode pengumpulan data yaitu wawancara dan dokumentasi. Metode analisis data pada penelitian ini adalah teori Miles dan Huberman. Berdasarkan hasil wawancara dan dokumentasi, Zoom Cloud Meeting dinilai efektif dalam meningkatkan mahārah kālam mahasiswa. Hal ini dikarenakan Zoom menyediakan fitur-fitur yang lengkap, sehingga komunikasi antara dosen dan mahasiswa dengan menggunakan bahasa Arab dapat terlaksana dengan baik. Metode yang digunakan dalam meningkatkan mahārah kālam adalah metode taqdimul qisshah dan muhadatsah. Sebagai media pembelajaran, Zoom memiliki kelebihan dan kekurangan. Kelebihan dari media tersebut adalah tersedinya fitur-fitur yang lengkap dan mendukung proses belajar mengajar, kapasitas ruang yang besar, fleksibel, dan kapasitas akses yang tinggi. Sedangkan kekurangannya adalah borosnya kuota internet, pembatasan media dan harus terhubung dengan jaringan internet yang kuat.